In silico Toxicity Prediction of Ethanol Extract of Cola rostrata (K. Schum.) Epicarp - Ajayi, Babatunde Ebenezer; Aina, Oluwafemi Segun; Odunlade, Albert Kolawole; Minari, Bamidele Joseph (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Abstract. The ethanol extract of the epicarp of Cola rostrata fruit has been reported to possess notable pharmacological properties, including anticancer, anti-inflammatory and antidiabetic effects; however, its toxicological profile remains understudied. This study evaluated the metabolism, excretion and toxicity properties of Gas Chromatography-Mass Spectroscopy-identified phytochemicals from C. rostrata epicarp. In silico analysis and molecular docking of components of the extract were carried out using ADMETlab2.0 platform and Autodock4 tools. Visualization of molecular binding interactions was done using Discovery Studio-2020. Ten of the 48 compounds in the extract, including 1-(4-Methoxyphenylazo)-2-phenoxynaphthalene, Anthiaergostan-5,7,9-trien-14.alpha.,15.alpha.-diol and 2-Hydroxychalcone, were predicted to have high probability of inducing liver injury, oxidative stress and inhibiting cytochrome-P450 enzymes. Molecular docking revealed that 1-(4-Methoxyphenylazo)-2-phenoxynaphthalene binds strongly to NADH dehydrogenase 1 (-7.78 kcal/mol) and CYP2C19 (-9.93 kcal/mol), with the compound interacting with Thr301, Leu361 and Leu366 at the active site of CYP2C19. 2-Hydroxychalcone binds strongly to CYP2C19 (-8.07 kcal/mol) and to Na+/K+-ATPase (-7.49 kcal/mol), while, Anthiaergostan-5,7,9-trien-14.alpha.,15.alpha.-diol binds strongly to CYP2C19 (-9.56 kcal/mol) and CYP1A2 (-8.71 kcal/mol). The extract showed strong potential to induce toxic outcomes. The abundance of antioxidant phytosterols in the extract may counterbalance the potential toxicity. While C. rostrata holds therapeutic potential, molecular interactions of its phytochemicals highlight risks of toxicity.